Life-Style Reflections On The Architecture Of The Single-Family House In Erbil City Based On The Income - Hadar Ihsan Ali; Mahmod Ahmad Alkayat (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The study aims to determine an existing pattern of living (lifestyle) in Erbil city and its reflection on architecture and dwelling unit components. A case study methodology has been approached, and 30 residential buildings have been selected to be analyzed in Erbil as the limit of the study. The buildings have been divided into three categories (Low, Mid, and High) based on the income of the families in the region of study. The observation and questionnaire methods have been conducted to reach the results. The observation factors were developed and have been applied to determine lifestyle patterns in Erbil city. A questionnaire has been developed to identify lifestyle patterns by asking people about their daily life patterns and how it was reflected in the architecture design of their dwelling unit. The paper determined three lifestyles in Erbil city about the income groups that were reflected in the dwelling unit’s component (the existence of dining room and dining furniture) and the pattern of family living in terms of social relations within single-family and the neighbors. The study concluded that there is a strong relationship among family members and with the neighbors, and the lifestyle is remarkably influenced by the families’ income.